ZnO, Cu-doped ZnO, Al-doped ZnO and Cu-Al doped ZnO thin films: Advanced micro-morphology, crystalline structures and optical properties - Dejam, Laya; Kulesza, Slawomir; Sabbaghzadeh, Jamshid; Ghaderi, Atefeh; Solaymani, Shahram; Țălu, Ștefan; Bramowicz, Miroslaw; Amouamouha, Mitra; shayegan, Amir hossein Salehi; Sari, Amir hossein (Results in physics, 2023)
•ZnO, mono- and co-doped ZnO with Cu and Al dopants fabricated by RF sputtering.•Advanced fractal features extracted from AFM images.•Advanced crystalline structures investigated by XRD spectra.•The CAZO thin film behaves like a good TCO in the visible area.•PL spectra investigated density of free carriers, effect of impurity on substituted levels, and conductivity. The thin film coatings composed of: undoped ZnO film, ZnO doped with Al, ZnO doped with Cu, and ZnO simultaneously doped with Al and Cu (co-doping) were separately deposited on quartz substrates using RF sputtering method with different targets. The advanced fractal features, crystalline structure and optical properties of sputtered samples were investigated by atomic force microscopy (AFM), X‐ray diffraction (XRD) and UV–vis spectroscopy. Microstructural studies revealed homogeneously granular structure of ZnO layer and axially oriented granular structure of AZO thin film. The transmission spectra of undoped, mono-doped and co-doped ZnO thin films were measured revealing relatively large transmittance of more than 80 % for un-doped and co-doped samples and less than that value for mono-doped thin films in both visible and infrared regions. CAZO thin film was found the most transparent thin film in the visible area being a prerequisite for good TCO. Analysis of absorption coefficients demonstrated that excitonic effects are invisible in mono-doped and co-doped samples. Also, PL spectra show that in these samples there are very high densities of free carriers and presence of impurities, which is important for conductivity of thin films as well as their optical applications. The optical band gap of ZnO thin films decreases by Cu doping from 3.12 eV to 3.09 eV and increases by Al doping to 4.30 eV, but remains exactly between those values in terms of co-doped sample (3.75 eV).